Implementing the Four Rs (4Rs) in Nutrient Stewardship for Tomato Production - Qingren Wang; Guodong Liu; Kelly Morgan; Yuncong Li (EDIS, 2016)
Fertilization plays a critical role in tomato production across the state of Florida. However, appropriate fertilization management depends on four major components (4Rs): right source, right rate, right placement, and right timing. Farming practices that follow the 4Rs can provide nutrients for optimal tomato productivity while minimizing the risk of nutrient losses and adverse environmental effects, both of which are important to the development of agricultural sustainability. This 6-page fact sheet discusses the 4Rs as well as conventional dry source fertilizers, controlled-release or slow-release source fertilizers, and liquid source fertilizers. Written by Qingren Wang, Guodong Liu, Kelly Morgan, and Yuncong Li, and published by the UF Department of Horticultural Sciences, October 2015.